Prognostic value of albumin-corrected anion gap in critically ill patients with sepsis-associated liver injury: a retrospective study - Jianjun Wang; Yonghai Peng; Zhaohui Hu; Xi Chen; Sirui Chen; Pei Yang; Xintao Zeng; Decai Wang (BMC Infectious Diseases)
Abstract Background Albumin-corrected anion gap (ACAG) is closely associated with the prognosis of many critical illnesses. However, the prognostic value of ACAG in sepsis-associated liver injury (SALI) is poorly understood. We explored the association between ACAG and patient prognosis in individuals diagnosed with SALI. Methods Data from patients with SALI admitted to the intensive care unit (ICU) between 2008 and 2022 were retrospectively analyzed. ACAG was calculated based on the first measurement of the anion gap and albumin level within 24 h of admission. The optimal cutoff value for ACAG was established using R statistical software. Kaplan-Meier analysis was conducted to compare mortality risks between the two groups, while multivariable Cox proportional hazards regression models were employed to examine the association between ACAG and mortality risk in SALI patients. To assess a potential dose-response relationship, restricted cubic splines (RCS) were applied. Lastly, subgroup analyses were carried out to investigate the correlation between ACAG levels and prognosis across different patient populations. Results A total of 443 critically ill patients with SALI were included in the lower (n = 342) and higher ACAG (n = 101) groups based on ACAG levels. No statistically significant differences were observed between the two groups regarding age, sex, or ethnicity (P = 0.12, 0.84, and 0.85, respectively). However, patients in the higher ACAG group exhibited a greater propensity for developing respiratory failure. The rates of ICU, in-hospital, 14-day, 28-day, and 90-day mortality were significantly elevated in the higher ACAG group (all P < 0.001). Higher ACAG levels were significantly associated with an increased mortality risk at multiple time points (all P < 0.001). ACAG levels and mortality showed a significant linear relationship. The impact of ACAG on mortality risk remained consistent across subgroups defined by age, sex, hypertension, diabetes, and respiratory failure, with no significant interactions observed (all P for interaction > 0.05). Conclusion ACAG serves as a significant independent predictor of mortality risk in patients with SALI. ACAG predicts both short-term mortality risk (such as ICU mortality) and long-term mortality risk (such as 90-day mortality). ACAG may serve as a valuable tool for prognostic assessment in patients with SALI with broad applicability.